Keteladanan Orang Tua Kristen dalam Pembentukkan Karakter Remaja Berdasarkan Kitab Galatia 5:22-23 - Nofriana Baun; Misael Boineno; Yulius Musa Natonis; Dominggus Y. Selan; Yunita Seran (Danum Pambelum: Jurnal Teologi dan Musik Gereja, 2023)
This article aims to explore and explain in depth the example of Christian parents to shape the character of Christian teenagers based on Christian values. The author uses descriptive qualitative research methods, through interviews and observations. The author concludes that the example of Christian parents in forming the character of teenagers at the Efata Oetimu Klasis Soe Service Post in instilling the value of love is through actions and words. Meanwhile, the value of joy is a form of parental example that expresses an atmosphere of joy within oneself, both in joy and sorrow. Character formation based on the value of peace is carried out through making peace with oneself and also making peace with all family members. Meanwhile, parents' value of patience is difficult to shape adolescent character through actions. This is influenced by the attitude of parents who lack the value of patience in themselves. The formation of adolescent character through an attitude of generosity is carried out by parents. The concrete thing to do is for parents to be generous to all family members. The value of kindness given by parents in shaping the character of teenagers is to do good things to everyone regardless of status. The values ​​of loyalty and gentleness are also practiced by the parents in the family. Meanwhile, character building with the value of self-mastery has not been implemented well in the family because the children who are born have their own characteristics, which can make parents' emotions unstable.